1981
DOI: 10.1007/bf00916840
|View full text |Cite
|
Sign up to set email alerts
|

Televised classroom events as distractors for reading-disabled children

Abstract: Three experiments examined the influence of videotaped classroom events on the academic performance and study behavior of reading-disabled and normally reading children in grades 1 through 6. In experiments 1 and 2a an experimenter-controlled presentation of these distractors resulted in performance decrements, the magnitude of which was greater for higher difficulty tasks. The distractor effects were similar for the two groups in this condition. However, when the children themselves were allowed to control th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The initial development of item wording and response alternatives was based on recommendations made by school district personnel, or were adapted from previous research (Lyle & Hoffman, 1972;Patton , Routh & Offenbach, 1981). Final wording and presentation order were set following a pilot administration of the questionnaire to 24 fifth grade students.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial development of item wording and response alternatives was based on recommendations made by school district personnel, or were adapted from previous research (Lyle & Hoffman, 1972;Patton , Routh & Offenbach, 1981). Final wording and presentation order were set following a pilot administration of the questionnaire to 24 fifth grade students.…”
Section: Methodsmentioning
confidence: 99%
“…Studies usi ng systematic observation of children in classroom settings have indicated that distractibility there may occur more frequently among students who have learning problems (Routh, 1979). Nevertheless, 20 years of distraction research, carried out with normal and special populations of children under controlJed laboratory conditions, has yielded an array of confusing, ambiguous findings which so far have been of little practical use to educators (Patton , Routh & Offenbach, 1981).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Experiments investigating the effects of different types of distraction during study have not always supported the distraction hypothesis (e.g., Doleys, 1976;Patton, Routh, & Offenbach, 1981). Experiment 2 investigated the possibility that certain distracting study conditions not unusual in a college environment would be a detriment to iearning.…”
Section: Methods Experimentsmentioning
confidence: 98%